Інтерпретація Т-подібного рогового виробу з могильника Острів - Дяченко, Д.Г. (Археологія, 2022)
Статтю присвячено Т-подібному роговому контейнеру з поховання 37 західнобалтського могильника
Острів у Пороссі. Розглянуто історію вивчення,
ареал поширення, хронологію та інтерпретацію
функціонального призначення цієї категорії предметів. The paper is devoted to one of the categories of equipment of a warrior of the 11th century, discovered at the Western Baltic
Ostriv burial ground in Porossia (Middle Dnipro region). The red deer antler item has a T-shaped form, the distance between two
longitudinal sections is 13.3 cm, and between the upper hole and the solid wall of the object is 11.3 cm. The lateral holes are not
symmetrical: the diameter of the larger one is 4.7 cm, the smaller one — 4 cm, and the upper one — 2.8 cm. Two small drilled
holes are located near the last one for fixing a stopper made of organic materials, with the subsequent suspension to the belt with
a rope. Near the smaller lateral hole was found an iron plate and the remains of the fabric in which it was wrapped. The weight
of the artefact is 190 gr.
We assume the sample from Ostriv is a container made from antler. The T-shaped form of the item when suspended by small
holes on the upper channel provided for the direction of the main load of the contents on the lower solid wall of the object. The
fabric-wrapped metal plate provided a much better sidewall overlap density and could withstand more weight pressure than
organic material tires. The contents of the container had to meet the needs of a person whose daily life is directly related to certain
military activities, possibly far from the place of permanent residence and regardless of weather conditions.
The study history, area of distribution, chronology, and interpretation of the functional purpose of this category of objects are
considered. From the given analogies, it is obvious that such a thing was not common, maybe even considered prestigious. We
believe that the container from Ostriv was used for compact storage of loose organic and mineral substances — salt, spices,
medicinal herbs, etc., preventing the ingress of moisture.
The issue of the container origin is debatable, as such artefacts are not typical for the South-East Baltic. Therefore, the Baltic
warrior could have obtained it in one of the distribution zones of antler containers at the end of the 10th — the beginning of the
12th century: within the settlement of the Western Slavs in the Elbe and Oder rivers in the north of modern Germany; adopted
from the Turkic population of the Eastern European steppes; or it should be connected with the workshop discovered in the Voin
stronghold in the Middle Dnipro River. We claim the last case to be the most promising.